A Text-Based Approach in English for Arts and Design: An ESP Course Design - Marsakawati, Ni Putu Era (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
English for arts and design is a vocational English developed to facilitate non-English students, studying visual design communication. The goal of the course is to enable the students to use English and communicate effectively in the context of visual design business. To achieve this learning goal, the lecturer should design a meaningful and effective course design.  Among various approaches to ESP course design, this article describes the text-based approach. Because the students are from a non-English department, this strategy will help them learn English more effectively. When the lecturer uses this approach, they provide students with sufficient scaffolding. These scaffolding are useful for assisting students to gain confidence in using English. Gradually, their learning goals can be achieved effectively.  Thus, this article aims to describe how to design an effective ESP course for Visual Design Communication students and report its implementation in the classroom. This paper will hopefully provide some practical insights in designing ESP courses and in using text-based approach  in ESP classrooms.